Final Sampling Bias in Haptic Judgments: How Final Touch Affects Decision-Making. (January 2018) - Mitsuda, Takashi; Yoshioka, Yuichi
When people make a choice between multiple items, they usually evaluate each item one after the other repeatedly. The effect of the order and number of evaluating items on one's choices is essential to understanding the decision-making process. Previous studies have shown that when people choose a favorable item from two items, they tend to choose the item that they evaluated last. This tendency has been observed regardless of sensory modalities. This study investigated the origin of this bias by using three experiments involving two-alternative forced-choice tasks using handkerchiefs. First, the bias appeared in a smoothness discrimination task, which indicates that the bias was not based on judgments of preference. Second, the handkerchief that was touched more often tended to be chosen more frequently in the preference task, but not in the smoothness discrimination task, indicating that a mere exposure effect enhanced the bias. Third, in the condition where the number of touches did not differ between handkerchiefs, the bias appeared when people touched a handkerchief they wanted to touch last, but not when people touched the handkerchief that was predetermined. This finding suggests a direct coupling between final voluntary touching and judgment.